Evidence-Based Practices and Treatments for Children with Autism - Reichow, Brian; Doehring, Peter; Cicchetti, Domenic V.; Volkmar, Fred R.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Autism spectrum disorders (ASDs) have been increasingly diagnosed in recent years and carries with it far reaching social and financial implications. With this in mind, educators, physicians, and parents are searching for the best practices and most effective treatments. But because the symptoms of ASDs span multiple domains (e.g., communication and language, social, behavioral), successfully meeting the needs of a child with autism can be quite challenging. Evidence-Based Practices and Treatments for Children with Autism offers an insightful and balanced perspective on topics ranging from the historical underpinnings of autism treatment to the use of psychopharmacology and the implementation of evidence-based practices (EBPs). An evaluation methodology is also offered to reduce the risks and inconsistencies associated with the varying definitions of key autism terminology. This commitment to clearly addressing the complex issues associated with ASDs continues throughout the volume and provides opportunities for further research. Additional issues addressed include: Behavioral excesses and deficits treatment Communication treatment Social awareness and social skills treatment Dietary, complementary, and alternative treatments Implementation of EBPs in school settings Interventions for sensory dysfunction With its holistic and accessible approach, Evidence-Based Practices and Treatments for Children with Autism is a vital resource for school psychologists and special education professionals as well as allied mental health professionals, including clinical child and developmental psychologists, psychiatrist, pediatricians, primary care and community providers.
Part I: Introduction -- Evidence-Based Practices in Autism: Where We Started -- Development, Procedures, and Application of the Evaluative Method for Determining Evidence-Based Practices in Autism -- On the Reliability and Accuracy of the Evaluative Method for Identifying Evidence-Based Practices (EBP) in Autism -- Part II: Treatment Reviews -- Evidence-Based Treatment of Behavioral Excesses and Deficits for Individuals with Autism Spectrum Disorders -- Evidence-Based Treatments in Communication for Children with Autism Spectrum Disorders -- Treatments to Increase Social Awareness and Social Skills -- Cognitive Behavioral Therapy in High Functioning Autism: Review and Recommendations for Treatment Development -- Psychopharmacology in Children with PDD: Review of Current Evidence -- Interventions that Address Sensory Dysfunction for Individual$1 (Bs with Autism Spectrum Disorders: Preliminary Evidence for the Superiority of Sensory Integration Compared to Other Sensory Approaches -- Dietary, Complementary, and Alternative Treatments -- Part III: Research to Practice -- The Role of Adaptive Behavior in Evidence-Based Practices for ASD: Translating Treatment to Functional Success -- Practicing Evidence-Based Practice -- The Implementation of Evidence-Based Practices in Public Schools -- Evidence-Based Practices in Autism: Where We Are Now and Where We Need to Go.s
Keywords: Philosophy (General).; Pediatrics; Psychiatry; Developmental psychology; Psychology; Child and School Psychology; Psychiatry; Education (general).; Pediatrics